Crack Propagation on the Surface of the Bottleneck of a Pressure Vessel Considering the Initial Crack Angle - Zhou, Xiuyun; He, Ruijie; Zhou, Ting; Liu, Zhen (Applied sciences, 2022)
In order to solve the impact on the accuracy of a life prediction model when the initial crack angle of the curved surface is not 0°, the traditional stress intensity factor model is revised by the non-linear regression analysis method, and an optimized crack growth model is established. This paper takes the surface of the bottle neck of the pressure vessel as the research object, and uses the finite element method to establish a simulation model with an initial crack angle of not 0°. By analyzing the stress intensity factors of different starting angles, the relationship between the correction factor F and the pressure vessel wall thickness h, the radius of curvature R of the joint surface between the bottle neck and the bottle body, the initial crack length L and the initial angle α are calculated. The modified stress intensity factor is used to optimize the crack growth model of the pressure vessel. The experiment proves that the accuracy of the pressure vessel life prediction model is improved.